Analysis of Realistic Game Graphics Development Using Photogrammetry Method - Isyrin Apridal, Fauzi; Hidayat, Rahmat; Afyenni, Rita (Faculty of Engineering, Universitas Brawijaya, 2024)
The development of realistic video game graphics has increasingly become a primary focus in the gaming industry. Among the technologies enabling this advancement, photogrammetry stands out for its ability to create highly accurate and realistic 3D models from real-world objects or environments. This study utilized RealityCapture software to process a dataset of flower pot images into a detailed 3D model. The photogrammetry process encompasses several critical stages: importing the image dataset, calibrating the camera to correct for lens distortions, reconstructing the 3D model from aligned images, refining the model to correct any inaccuracies, and finally integrating the model into a game engine for use. The results illustrate that photogrammetry can significantly enhance the realism of video game graphics, offering a level of detail and authenticity that traditional modeling techniques may struggle to achieve. Despite some technical challenges, such as high hardware requirements and large data sizes, photogrammetry reduces the time and cost of creating graphic assets while delivering an immersive experience for players.